Disaster Knowledge Related to Disaster Management Among Teenagers - Karinawati, Sindy; Anam, Agus Khoirul (Poltekkes Kemenkes Malang, Campus III Blitar, 2024)
Damage to school infrastructure, systems, and human resources can affect the quality of education. The introduction and provision of knowledge on disaster risk reduction in the education sector needs to be given to school residents in disaster prone areas. The purpose of this research is to know Knowledge of Disaster Safe Education Unit based on 3 pillars of National Disaster Management Agency in Disaster Prone Area II. Descriptive research design. The population of SMKN 1 Nglegok residents who are in disaster prone area II. A sample of 47 school residents with stratified sampling technique. Data collection using questionnaire. The results show that there are still some 41.6 percent of the school's residents have enough knowledge, and very few of the 6.3 percent schoolchildren have less knowledge. This is due to the lack of information and existing school facilities are less supportive and need to improve the experience owned by school residents. Suggestions from the research are expected to provide training or counseling about disaster risk reduction in schools, improve the knowledge of school residents, especially teachers and administrative staff about DRR in schools so as to realize the School of Disaster Safe Education Unit with proper implementation and school residents can increase preparedness in facing disaster becomes better.